PENGARUH PROFITABILITAS, SOLVABILITAS, DAN DUKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Ni Made Yuliana Yunita; Komang Fridagustina Adnantara; Tiara Kusumadewi (Journal Research of Accounting, 2020)
The timeliness of submitting financial statements is a important characteristic for accounting information because of information that has passed by market participants in the process of making decision for investment, because of the information submitted could be lose its relevance value. The purpose of this research is to analyze profitability, solvency, and company size of the audit report lag on listed manufacturing companies on the Indonesia Stock Exchange period 2016 – 2018. This research used 128 population. The research sample was taken using purposive sampling method, thus obtaining 98 samples. Data analysis techniques using documentation by analyzing financial data in the listed report financial manufacturing companies on the Stock Exchange in 2016 – 2018. Testing is done with the classic assumption test, multiple linear regression test, analysis coefficient of determination, F test, and t test. The results showed profitability, solvency, and company size have a positive effect and significant to the audit report lag to the listed audit report lag on the Indonesia Stock Exchange in 2016 – 2018.